Tantangan Konversi Bank Konvensional Menjadi Bank Syariah di Aceh Berdasarkan Qanun Lembaga Keuangan Syariah No 11 Tahun 2018 (Sharia Faculty Islamic Economic Law Study Department, 2020)
The presence of the Islamic Financial Institution Qanun No 11 in 2018 is a special right for Aceh and has brought a breath of fresh air to the development of the Islamic banking industry in Aceh, a number of conventional banks in Aceh are required to convert to Islamic banks, The purpose of this study is to explain the procedure for accelerating the conversion of unconventional banks to Islamic banks in Aceh and to explain the challenges of banking institutions with the obligation to convert financial institutions in Aceh. The obligation to convert a conventional bank into a sharia bank is clearly as stipulated in article 6 points e and d, although the process of converting a conventional bank to a sharia bank is not found directly in the qanun, but every bank that does the conversion must refer to BI regulations namely PBI No. 11 / 15 / PBI-2009, this is as explained in article 12